Pleiotropic effects of rosuvastatin on microvascular function in type 2 diabetes - Parson H (Diabetes, Metabolic Syndrome and Obesity, 2010)
Henri K Parson, Meredith A Bundy, Charlotte B Dublin, Amanda L Boyd, James F Paulson, Aaron I VinikLeonard R. Strelitz Diabetes Center, Department of Internal Medicine Eastern Virginia Medical School, Norfolk, Virginia, USAAbstract: Rosuvastatin is known to reduce low-density lipoprotein (LDL)-cholesterol and improve endothelial function. In addition to lipid-lowering, statins may exert pleiotropic (nonlipid lowering) effects on microvascular function. We compared the neurophysiological and vascular responses of dietary control and treatment with 10 mg of rosuvastatin in 16 subjects with neuropathy and established type 2 diabetes. Skin blood flow (SkBF) measurements were measured at baseline, after 18 weeks of diet, and after 18 weeks of diet and treatment with rosuvastatin in response to local warming and ischemia reperfusion. The study results show that total cholesterol (196.50 ± 8.02 to 134.88 ± 10.86 mg/dL) and LDL-cholesterol (114 ± 10.4 to 63.4 ± 8.48 mg/dL) decreased significantly after 18 weeks of rosuvastatin, but not after 18 weeks of diet. Neuropathy scores decreased from 8.34 ± 1.26 at baseline to 6.00 ± 0.90 after rosuvastatin treatment. Basal SkBF was significantly different from baseline, 6.81 ± 0.42 to 9.92 ± 0.78 after rosuvastatin treatment (P ≤ 0.001). These results indicate that rosuvastatin therapy positively changed basal SkBF and measures of neurovascular function. Although there was a profound lipid lowering, it is not clear that this mediated the increases in SkBF and decreases in neuropathy scores.Keywords: neurovascular function, rosuvastatin, diabetes